Going ape : Florida's battles over evolution in the classroom - Haught, Brandon (Gainesville : University Press of Florida, 2014)
In this book, Haught chronicles the war over teaching evolution in Florida's schools, from the first shouts of religious persecution and child endangerment in Tallahassee in 1923 to the forced delays and extra public hearings in state-level textbook adoptions today.
"Between the devil and the deep blue sea" -- "Un-American, atheistic, subversive, and communistic" -- "A spirit of compromise and conciliation" -- "A history of hoaxes, deception, and deceit" -- "A conspiracy to destroy the faith of children" -- "It was historic, wasn't it?" -- "One of the primal evils in our country" -- "There are razor blades in that apple" -- "I want God to be part of this" -- "Who gets to decide what is science?" -- "Standing up for the little guy."
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Evolution (Biology) -- Study and teaching -- Florida; Evolution (Biology) -- Philosophy; Creationism; Religion and state; Religion and science; Biological Evolution; Teaching; Religion and Science; Schools; Florida; SCIENCE -- Life Sciences -- Evolution; Creationism; Evolution (Biology) -- Philosophy; Evolution (Biology) -- Study and teaching; Religion and science; Religion and state; Florida; SCIENCE / History; Electronic books